Actynomicosis of the abdomen mimicking acute appendicitis - Molina Davila, David; Espitia, Francisco Terrazas; Figueroa, Alejandro Corona; Hernandez, Jose Donis; Cal Y. Mayor, Jimena Gonzalez (International Surgery Journal, 2019)
Bacteria of the genus Actinomyces are non-spore-forming filamentous, Microaerophilic or strict anaerobic, Gram-positive bacilli, mainly belonging to the human commensal flora of the oropharynx, gastrointestinal tract, and urogenital tract; Actynomicosis israelii is most frequently isolated in human infection by this bacteria (90% of the cases), and is a very rare, generally a polymicrobial granulomatous infection which affects the cervicofacial (55% of all cases), abdominopelvic (22%) and thoracic (15%) regions, causing formation of abscesses, woody fibrosis and sinus discharge of characteristic sulfur granules. We present the case of a 42 year old patient with no prior medical history who presented to the emergency room with acute onset abdominal pain in the lower right quadrant, leukocytosis and neutrophilia, as well as ultrasonographic images which suggested acute appendicitis, the patient underwent laparoscopic appendectomy and cultures of abscesses surrounding the appendix were positive for A. israelii, which was also isolated in the histopathological specimen. The patient underwent antimicrobial treatment with ampicilin-sulbactam for a three month period postoperatively.